Entre máquinas e esculturas: mulheres levantadoras de peso - Araújo, Leonardo Vasconcelos de (2021)
With this research I intend to show how the daily task of lifting weights can represent not only the manufacturing of a strong (muscular) body, but also the constitution of a subjective anchorage. Weight is, therefore, a limit, a matter that enables the productive effort of life's reinvention through the creation of a powerful body, capable of establishing new relationships with the world and its objects. To do this, I launched myself into the experience of following three female weighlifters, who, within their particular practices, fashioned other corporalities, expanding the body's frontiers and challenging socially imposed boundaries. In this sense, the question the guides my effort is this: how the bodily practice of female weightlifters impact the archive and the repertoire of a certain image of the female body as frail, delicate and incapable of exert violence? I depart, therefore, of the assumption that my interlocutors's body potency, as well as their image, act as a disruptive force against a certain idea of femininity in our social landscape. In other words, their bodies seems to question power relations grounded on the sexual difference, on a gender binarism produced and supported by the heteronormative discourse. For that purpose my work is divided in three moviments. On the first, "Notes of an amatour athlete-researcher" I present to you my methodological route, built in conjunct with a series of bodily experimentations activated by the somatic sharing set with my interlocutors. On the second, "'Woman can be whattever she wants': manufacturing a female muscular body", I present to you the production process of my interlocutors's bodies, taking into consideration the mobilized technologies, the scenarios in which they are produced, the affect regimes, the time and training necessary to take them to their limits, the injuries faced, the diets, the disciplinning and the regulations required for them to perform well on competitions. On the third moviment, finally, my aim is to show the athletes in action, on their different sportive modalities. Competitions are of fundamental importance to this investigation, to the extent that they represent the ultimate goal of all their bodily and subjective engaging. This is due not only through the validation it promotes of their bodily practice but also because they make possible a financial return that allows them to continue their careers. In addition, by way of the diffractions mobilized along the “field-body” work, I address some of the implications resulting from the athletes' corporal practice, taking into account the possible interweavings between physical and political empowerment.